(untitled) (Scientific journal of the Fergana State University, 2026)
This study explores the integration of ChatGPT-supported collaborative argumentation and critical skills technology to enhance EFL students’ written argumentative competence. Through analysis of open-source literature, the findings reveal significant improvements in argument quality, critical thinking, and collaboration. The model is particularly beneficial in EFL contexts like Uzbekistan, offering an innovative approach to developing academic writing skills.